2011
DOI: 10.1007/s11249-011-9755-0
|View full text |Cite
|
Sign up to set email alerts
|

In Situ TEM Observation of the Behavior of an Individual Fullerene-Like MoS2 Nanoparticle in a Dynamic Contact

Abstract: Inorganic fullerene-(IF)-like nanoparticles made of metal dichalcogenides (IF-MoS 2 , IF-WS 2 ) have been known to be effective as anti-wear and friction modifier additives under boundary lubrication. The lubrication mechanism of these nanoparticles has been widely investigated in the past and even if the exfoliation and third body transfer of molecular sheets onto the asperities constitute the prevalent mechanism for the improved tribological behavior of IF nanoparticles, it has also been suggested that a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 16 publications
1
56
1
Order By: Relevance
“…5, it shows that the lubricants with CNC nanoparticle addition have a lower friction coefficient than the pure oil lubricant, In fact, the main favorable benefit of the nanoparticle as oil additives is attributed decidedly to the following two effects, namely, ball bearing mechanism [26,27] and third body materials forming mechanism [28]. Specifically, the present frictionless phenomenon can be most likely attributed to the fact that a ball bearing effect induced by the spherelike multilayered structure of the CNC particles [29][30][31][32]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…5, it shows that the lubricants with CNC nanoparticle addition have a lower friction coefficient than the pure oil lubricant, In fact, the main favorable benefit of the nanoparticle as oil additives is attributed decidedly to the following two effects, namely, ball bearing mechanism [26,27] and third body materials forming mechanism [28]. Specifically, the present frictionless phenomenon can be most likely attributed to the fact that a ball bearing effect induced by the spherelike multilayered structure of the CNC particles [29][30][31][32]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…At still higher pressures the particles are crushed to form a low shear strength layer-lattice film. The onset of exfoliation of IF-MoS 2 has also been observed using in situ TEM [233]. Because of this pressure-dependent exfoliation, IF particles give lower friction coefficient at high than at low pressure [231].…”
Section: Nanoparticle Additive Research; 1990 To Presentmentioning
confidence: 80%
“…For these reasons, 2H-WS 2 NPs could be more convenient to employ as lubricant nanoadditives in high-pressure tribological applications. A large number of research studies have attempted to explain the mechanism of action of WS 2 NPs by proposing many hypotheses [16][17][18][19][20][21][22]. During the last 20 years, the attention has focused on IF-WS 2 NPs, and their mechanism of action has been studied in numerous publications.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was investigated by Golan [23] who used multiple-beam interferometry in the surface force apparatus to show that there was no evidence for 'rolling friction,' and the low values of the coefficient of friction (COF) can be explained by the friction-induced transfer layers of WS 2 to the lubricated contact surfaces. However, some recent studies [21,22], which investigated the rolling mechanism of IF NPs in HRSEM and TEM-AFM in high-and, respectively, low-pressure contacts showed that well crystallized, spherically shaped IF NPs can reduce friction through a rolling mechanism. These studies were carried out on atomically smooth silica wafers [21], and the question arises whether in real contact conditions, in which nanoparticles could get trapped or jammed between the surface asperities, the rolling motion is still enabled.…”
Section: Introductionmentioning
confidence: 99%